ИНТЕНСИВНАЯ ТЕХНОЛОГИЯ ОТКОРМА МОЛОДНЯКА ПРИВОЗНОГО СКОТА (Scientific journal of the Fergana State University, 2023)
In the article it is given information about economic productivity of using grain hay fattening in different ways on high-calorie of fodder ration of calves of cattle brought from other places.